Teaching strategies: How do teachers in remote area survive during remote learning? - Amelia, Rini; Istianah, Tia Nur (ELT Forum: Journal of English Language Teaching, 2021)
During the pandemic of COVID-19, remote learning has been very highlighted. This environment creates huge challenges especially to those teaching in remote areas. Drawing on them, this descriptive qualitative study aims to explore teaching strategies applied there. In collecting the data, interviews and questionnaires were given to two English teachers of a Junior High School in Aranio, Banjar Regency. The results show that they have to face some challenges such as the limitedness of internet access and low motivated students when implementing remote learning. Due to this condition, they need to survive by making some efforts such as creating and using interesting teaching modules, coordinating with the related parties, carrying out blended learning, conducting home visit and setting up offline classes because of no possibility for online learning. Through this study, other teachers are kindly informed on the applicable teaching strategies to create effective remote learning experiences in remote areas.